PROBLEM ISSUES OF OUT-OF-COURT SETTLEMENT OF ECONOMIC DISPUTES - Zhmur, Nataliia; Oleniuk, Anastasia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The purpose of the article is to highlight the issue of legal consolidation of out-of-court methods of settling commercial disputes, as well as the difficulties that arise in practice in the case of their use. Methods: methods of analysis, comparison and synthesis are used in the course of work. The method of analysis was used in the study of Ukrainian legislation in the context of out-of-court settlement of commercial disputes, the method of comparison – in the process of identifying similar and different aspects in the mediation procedure in Ukraine and abroad. Results: methods of out-of-court settlement of commercial disputes are investigated. Their advantages and disadvantages are analyzed. The problems of legislative regulation are substantiated, as well as the difficulties that may arise in the practice of out-of-court settlement of conflicts. Some comparative aspects of the mediation procedure in Ukraine and the countries of the European Union are given. Discussion: extrajudicial methods of settling commercial disputes. The authors came to the conclusion that in the event of a commercial dispute, the subject may, at its own discretion, either use extrajudicial methods of dispute resolution or go to court. Exceptions are only a few cases where filing a claim is a prerequisite for going to court. Each of the out-of-court methods of settling commercial disputes has its advantages and can, and in some cases should be used. However, for their effective use it is necessary to improve the current legislation of Ukraine, to regulate the mediation procedure by adopting the Law of Ukraine «On Mediation», to eliminate shortcomings in existing legislation.